PRESERVING PROVERBS IN THE DIGITAL AGE: A QUALITATIVE STUDY ON STAKEHOLDER PERCEPTIONS OF ARTIFICIAL INTELLIGENCE FOR ACEHNESE LANGUAGE HERITAGE - Hajar, Ibnu; Husna, Asmaul; Aulia, Muhammad Kahfi; Muntazar, T. (STMIK Indonesia Banda Aceh, 2026)
This qualitative study investigates the perceived opportunities and challenges of developing an artificial intelligence (AI) application for preserving Acehnese proverbs (Hadih Maja), a critical yet endangered component of cultural heritage. Conducted as a multi-stakeholder feasibility study, it engages academics (linguists, anthropologists, AI/data scientists) and cultural custodians (tokoh adat) in North Aceh and Lhokseumawe, Indonesia. Through reflexive thematic analysis of in-depth interviews, the research reveals a dualistic landscape. Stakeholders recognize AI’s transformative potential as a bridge for intergenerational engagement, enabling interactive, mobile-based learning for youth. However, this promise is counterbalanced by formidable socio-technical hurdles. Key challenges include the fundamental